1998
DOI: 10.1007/s002239900419
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and Coronary Atherosclerosis in Asymptomatic Postmenopausal Women

Abstract: Estrogen deficiency is a risk factor for osteoporosis and coronary artery disease. Osteoporosis can be evaluated by measuring bone mineral density (BMD). Coronary atherosclerotic burden can be evaluated by measuring coronary calcium using electron beam computed tomography (EBT) of the heart. We compared coronary calcium scores in 45 asymptomatic postmenopausal women with normal and low BMD. BMD of the lumbar spine and proximal femur was measured by dual X-ray absorptiometry (DXA), and coronary calcium was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
3
11

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(159 citation statements)
references
References 31 publications
9
136
3
11
Order By: Relevance
“…Previously, conflicting results have been reported on the effect of cardiovascular diseases on BMD. Although arterial hypertension was associated with an increased BMD in one study [27], a reduced BMD was found by other investigators in subjects with arterial hypertension, as well as in patients with ischaemic heart diseases [28][29][30][31][32]. Thus, if ischaemic heart diseases cause a reduced BMD, LD may actually affect BMD positively, as we found a similar BMD in subjects treated with LD due to cardiovascular diseases as in healthy nonusers of LD.…”
Section: Study Strengths and Limitationssupporting
confidence: 67%
“…Previously, conflicting results have been reported on the effect of cardiovascular diseases on BMD. Although arterial hypertension was associated with an increased BMD in one study [27], a reduced BMD was found by other investigators in subjects with arterial hypertension, as well as in patients with ischaemic heart diseases [28][29][30][31][32]. Thus, if ischaemic heart diseases cause a reduced BMD, LD may actually affect BMD positively, as we found a similar BMD in subjects treated with LD due to cardiovascular diseases as in healthy nonusers of LD.…”
Section: Study Strengths and Limitationssupporting
confidence: 67%
“…Lipids have been shown to accumulate in bones of rats and blood vessels around bone in patients with osteo porosis [22,23] . Osteoporosis has been associated with both atherosclerosis and vascular calcification [24][25][26] . Serum lipid levels may alter bone mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic control of bone mass is polygenic and the specific genes involved are beginning to be enumerated, such as genetic variants/mutations of vitamin D and estrogen receptors (Mitchell & Yerges-Armstrong 2011). Recent attention has been given to atherogenic conditions with low HDL plasma levels as factors compromising bone health, and numerous associations, have been revealed between lower bone mass and cardiovascular diseases (Banks et al 1994, Uyama et al 1997, Barengolts et al 1998, von der Recke et al 1999, Hegsted 2001, Yamaguchi et al 2002, Poli et al 2003, Adami et al 2004, Orozco 2004. In accordance, a positive correlation between plasma HDL levels and bone mass has been reported by epidemiological studies (reviewed in Ackert-Bicknell (2012)), suggesting that, in addition to protecting against atherosclerosis, HDL contribute to a healthy environment for bones.…”
Section: Introductionmentioning
confidence: 99%